P618 Mycoplasma genitalium testing in clinical practice: prevalence and resistance rates in a south london sexual health clinic. (14th July 2019) - Wallis, Emma; Hamzah, Lisa; Nori, Achyuta
Abstract : Background: The British Association of Sexual Health and HIV recommends testing for Mycoplasma genitalium (MG) in clinically indicated conditions (CIC) (non-gonococcal urethritis (NGU); epididymitis; pelvic inflammatory disease (PID); contacts of MG; test of cure (TOC)). MG testing was implemented in September 2018 in a large urban sexual health service. We aimed to assess the prevalence and antimicrobial resistance of MG in this clinic population after a 6-weeks embedding period. Methods: All patients diagnosed with a CIC and tested for MG between 28/10/2018-18/12/2018 were included. MG testing was performed using Aptima Mycoplasma genitalium assay (AMG; Hologic); confirmatory testing and resistance testing for macrolides and fluoroquinolones was performed at the Public Health England reference laboratory. Results: The 371 individuals tested for MG were predominantly male (77%), heterosexual (78%) and Caucasian (46%) and 85% tested per guidance. 18% were positive for MG. 38% (25/65) were positive using AMG but had negative confirmatory test and no resistance results. 18% with MG were co-infected with another sexually transmitted infection (9 chlamydia; 2 gonorrhoea; 2 trichomonas). The prevalence of MG by testing indication was: contacts of MG (33%, 11/33), TOC (25%, 3/12), NGU/epididymitis (17%, 38/229), PID/cervicitis (11%, 5/44) and inappropriately tested (14%, 7/51). 38% of MG had resistance; 34% macrolides; 8% fluoroquinolones; 3% both. Macrolide resistance was identified on the 23SrRNA gene at loci A2058G (45%) and A209G (55%), all fluoroquinolone was on the parC gene. Conclusion: We report a high MG prevalence in this population with high rates of resistance, the majority of which is macrolide. We recommend resistance guided therapy in view of high macrolide and fluoroquinolone resistance. Positive RNA detection with negative DNA detection is concerning and may either represent very low bacterial loads, a biological false positive result of AMG or a false negative result of the confirmatory test. Disclosure: No significant relationships.